2014
DOI: 10.1177/1932296813517058
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Coronary Intervention in Patients With Diabetes

Abstract: Over 170 million people worldwide have diabetes mellitus (DM), with an increasing proportion of these patients diagnosed in the developing world.1 Despite medical advances in prevention of coronary artery disease (CAD), the rising prevalence of DM threatens to increase the global burden of cardiovascular disease in the next 2 decades.2 Currently, patients with DM compose 25% to 30% of all patients undergoing coronary artery revascularization.3 Up to 60% of patients presenting with acute myocardial infarction m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 59 publications
0
27
0
4
Order By: Relevance
“…Thus, whilst FFR is often seen as a binary assessment of ischemia, the absence of FFR detected ischemia in the setting of such rapid progression may not necessarily be reassuring. In the multivariate analysis in this study, insulin requiring DM and prior revascularization were identified as predictors of increased risk for DLF, both characteristics associated with increased burden, faster atherosclerosis progression, and worse outcomes .…”
Section: Discussionmentioning
confidence: 78%
“…Thus, whilst FFR is often seen as a binary assessment of ischemia, the absence of FFR detected ischemia in the setting of such rapid progression may not necessarily be reassuring. In the multivariate analysis in this study, insulin requiring DM and prior revascularization were identified as predictors of increased risk for DLF, both characteristics associated with increased burden, faster atherosclerosis progression, and worse outcomes .…”
Section: Discussionmentioning
confidence: 78%
“…[11][12][13][14] Although new generation drug eluting stents have also been shown to provide improved safety and efficacy compared with balloon angioplasty, bare metal stents, and early generation drug eluting stents among patients with diabetes, such patients, particularly when they need treatment with insulin, have a high ischaemic risk. [15][16][17][18] Increased platelet and thrombin reactivity and decreased response to therapeutic agents including aspirin and clopidogrel have been described in patients with diabetes. 19 20 Whether diabetes should be taken into consideration in the selection of the most appropriate duration of DAPT remains unclear.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Therefore, DM can result in vascular lesions arising from multiple mechanisms such as vasodilation disorder, platelet accumulation, thrombosis, inflammation, vascular remodelling, among others. Intensive blood glucose control can reduce the occurrence of cardiovascular events in type 1 DM, but no significant benefit was obtained in people with type 2 DM with an HbA1c level ≤ 7.0% [21,22]. Further research found that in the BMS implanted population, HbA1c levels were negatively correlated with BMS-ISR, but were not significantly correlated with DES-ISR [23].…”
Section: Discussionmentioning
confidence: 99%